Hydrated lanthanum oxide-modified diatomite as highly efficient adsorbent for low-concentration phosphate removal from secondary effluents. (1st February 2019) - Wu, You; Li, Xiaoming; Yang, Qi; Wang, Dongbo; Xu, Qiuxiang; Yao, Fubing; Chen, Fei; Tao, Ziletao; Huang, Xiaoding
Abstract: The requirement to the phosphorus (P) emission from wastewater treatment plants (WWTPs) is becoming increasingly strict, which makes an advanced treatment for the low-concentration phosphate removal from secondary effluents indispensable. In present work, hydrated lanthanum (La) oxide-modified diatomite composites (La-diatomite) were fabricated by a facile method and employed as the highly efficient adsorbent for the low-concentration phosphate removal from simulating secondary effluents. Comparative experiments indicated that the La-diatomite treated by 0.1 mol/L LaCl3 exhibited the highest La availability (P/La molar ratio of 2.30) and performed good selectivity to phosphate adsorption even with the coexistence of competing anions and humic acid. The maximum P adsorption capacity reached to 58.7 mg P/g and the 96% P was removed quickly within 30 min at initial phosphate concentration 2 mg P/L. Insignificant La leaching was observed during the process due to the La stabilization by macroporous diatomite. Eight cycles of adsorption-desorption experiments revealed that the excellent repeated use property of La-diatomite. At the column test, La-diatomite showed superior treatment capacities of 3455 kg water/kg La-diatomite for simulated secondary effluents. The La-diatomite maintained high and stable adsorption effectiveness in wide pH range, which should be attributed to the synergistic effect of electrostatic interactions, ligand exchange and Lewis acid-based interaction. This work might provide a candidate for low-concentration phosphate removal from secondary effluent to alleviate the eutrophication. Graphical abstract: Image 1 Highlights: La-diatomite possessed a high removal efficiency to low-concentration phosphate. La-diatomite exhibited the maximum adsorption capacity of 58.7 mg P/g. Phosphate adsorption was a pH-independent process. La-diatomite showed superior treatment capacity for simulated secondary effluents. The underlying adsorption mechanisms were elucidated in detail.